The Effect of 4C Skills on the Work Readiness of Beauty Vocational School Students in the Mamminasata Region - Salsabila; Andi Nur Maida; Hamida Suryani (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
This study investigates the extent to which collaboration, communication, creativity, and critical thinking skills influence the work readiness of beauty vocational students in the Mamminasata region. An associative quantitative research design was employed, and data were collected from 101 students enrolled in three public vocational schools using validated Likert-scale questionnaires. The dataset was analyzed through descriptive statistics, classical assumption tests, and simple and multiple linear regression analyses. The results demonstrate that all four components of the 4C framework significantly contribute to students’ work readiness. Communication emerged as the strongest predictor (β = 0.417; R² = 0.514), followed by critical thinking (β = 0.244; R² = 0.401), collaboration (β = 0.238; R² = 0.261), and creativity (β = 0.232; R² = 0.099). The simultaneous model accounted for 64.8% of the variance in work readiness (R² = 0.648; F = 44.267; p < 0.001), indicating a substantial cumulative influence of the four skills. These findings underscore the pivotal role of 4C competencies in enhancing vocational students’ preparedness to meet contemporary industry demands. The study highlights the imperative for integrating 4C-oriented instructional strategies into vocational education to strengthen the alignment between school-based learning and the competency standards required in the beauty sector. The results provide empirical evidence that may inform curriculum development, pedagogical decision-making, and policy initiatives aimed at improving graduates’ transition into the workforce.